ANALISIS MANFAAT PELAYANAN KESEHATAN YANG DITERIMA PASIEN BPJS KESEHATAN DI PUSKESMAS LEMPAKE KOTA SAMARINDA TAHUN 2015 - Herry Farjam; Nita Violen Tamaela (Universitas Widya Gama Mahakam Samarinda, 2016)
As organizer of social health insurance, social security health agencies continue to work so that all health facilities in Indonesia to support the passage of the health insurance program optimally so that all participants BPJS health benefit services. The purpose of this study was to determine the benefits of health care received by patients in health centers health BPJS participants Lempake cities Samarinda 2015 consists of variable promotive, preventive care, and curative services.The research method used is descriptive quantitative survey approach. The total sample is 100 patients. Data analysis using frequency distribution. Resulth of analysis using frequency distribution of 100 respondents showed that patients benefit as much as 89 respondents promotive services, patients feel the benefits of preventive care as much as 66 respondents, and patients feel the benefits of curative services as much as 95 respondents.